2020
DOI: 10.3390/app10196871
|View full text |Cite
|
Sign up to set email alerts
|

Inductive Imaging of the Concealed Defects with Radio-Frequency Atomic Magnetometers

Abstract: We explore the capabilities of the radio-frequency atomic magnetometers in the non-destructive detection of concealed defects. We present results from the systematic magnetic inductive measurement of various defect types in an electrically conductive object at different rf field frequencies (0.4–12 kHz) that indicate the presence of an optimum operational frequency of the sensor. The optimum in the frequency dependence of the amplitude/phase contrast for defects under a 0.5–1.5 mm conductive barrier was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…We have previously shown that for conductive objects an optimum value within a 1-2 kHz frequency range can be identified, which maximises the amplitude and contrast of features (defect, edge signatures) observed in the inductive images [7]. Similar behaviour was seen in magnetically permeable objects, but where the optimum values were shifted to a higher frequency range [21].…”
Section: Object Mapping -Spatial Scanmentioning
confidence: 69%
See 2 more Smart Citations
“…We have previously shown that for conductive objects an optimum value within a 1-2 kHz frequency range can be identified, which maximises the amplitude and contrast of features (defect, edge signatures) observed in the inductive images [7]. Similar behaviour was seen in magnetically permeable objects, but where the optimum values were shifted to a higher frequency range [21].…”
Section: Object Mapping -Spatial Scanmentioning
confidence: 69%
“…MIT provides a portfolio of measurements addressing a wide range of contemporary challenges in applied physics. In the area of non-destructive testing (NDT), inductive measurements enable detection of defects either covered by insulation or concealed within the object structure [3][4][5][6][7]. Immediate applications of the technology lie in the energy sector where corrosion under insulation is responsible for a significant fraction of the losses in the transport and storage of oil and gas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simplicity in tuning the two-photon resonance effectively bypasses the need to adjust transverse field/gradient field setpoints that would normally be required in bias field tuning. 18 Reinforcing this is an analysis of the SNR of the two configurations in Fig. 4.…”
mentioning
confidence: 92%
“…In 2001, Griffiths [1] proposed an imaging technique based on inferring one or more of the three passive electromagnetic properties (conductivity σ, permittivity and permeability µ) to produce images on the basis of the response to a position dependent oscillating magnetic field. Several denominations are used to identify this kind of methodologies, among which electromagnetic induction imaging (EII) [2], electro-magnetic tomograhy (EMT) [3], magnetic induction tomography (MIT) [4,5], and also mutual inductance tomography (same acronym) [6], the latter three stressing the potential of the technique to provide 3D mapping. A review on the subject was recently authored by Ma and Soleimani [7].…”
Section: Introductionmentioning
confidence: 99%